Report of the Working Group on Exports for Formulation of the Ninth Five Year Plan - Planning Commission (Planning Commission, 1996)
The Working Group on Exports was set up by the Planning Commission in the context of formulation of the 9th Five Year Plan (1997-2002), under the Chairmanship of Shri Tejendra Khanna, Secretary, Ministry of Commerce, Government of India. The Working Group included among members senior officials of Ministry of Commerce, DGFT, Department of Customs, Exim Bank, ECGC, leading Chambers of Commerce and Industry such as ASSOCHAM, FICCI and CII and export organisations such as ITPO, FIEO, EEPC, AEPC and APEDA. Dr.(Mrs.) V S Bharucha, Economic Adviser, Ministry of Commerce served as the Member- Secretary. The details of members of the Working Group are at annexure I.
Government of India Ministry of Commerce
Government of India Ministry of Commerce